2024
DOI: 10.1002/jmv.29386
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering head and neck cancer microenvironment: Single‐cell and spatial transcriptomics reveals human papillomavirus‐associated differences

Hansong Lee,
Sohee Park,
Ju Hyun Yun
et al.

Abstract: Human papillomavirus (HPV) is a major causative factor of head and neck squamous cell carcinoma (HNSCC), and the incidence of HPV‐associated HNSCC is increasing. The role of tumor microenvironment in viral infection and metastasis needs to be explored further. We studied the molecular characteristics of primary tumors (PTs) and lymph node metastatic tumors (LNMTs) by stratifying them based on their HPV status. Eight samples for single‐cell RNA profiling and six samples for spatial transcriptomics (ST), compose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…These included CD19, MS4A1 (B cell), CD3E, CD3D (T cell), CD4 (CD4T cell), CD8A, CD8B (CD8T cell), NCAM1 (NK cell), IL3RA, CLEC4C, NRP1, ITGAX, CD1C (DC), MS4A7, CD68, CD14, CD163 (monocyte), SLC4A10 (Mucosal‐associated invariant T cell; MAIT), TRGC1, TRDC (gamma‐delta T cell; gdT), PPBP, PF4 (platelet), and HBB, HBA1 (red blood cell). 63 , 64 …”
Section: Methodsmentioning
confidence: 99%
“…These included CD19, MS4A1 (B cell), CD3E, CD3D (T cell), CD4 (CD4T cell), CD8A, CD8B (CD8T cell), NCAM1 (NK cell), IL3RA, CLEC4C, NRP1, ITGAX, CD1C (DC), MS4A7, CD68, CD14, CD163 (monocyte), SLC4A10 (Mucosal‐associated invariant T cell; MAIT), TRGC1, TRDC (gamma‐delta T cell; gdT), PPBP, PF4 (platelet), and HBB, HBA1 (red blood cell). 63 , 64 …”
Section: Methodsmentioning
confidence: 99%
“…41 Moreover, spatial transcriptomics analysis of the distribution of immune cells by HPV infection status revealed that a high proportion of lymphoid cells was detected in HPV-positive patients, while a higher representation of epithelial and endothelial cells was found in HPV-negative patients. 42 Also, HPV-positive and HPV-negative HNSCCs show distinct metabolic profiles. HPV-negative tumors prioritize metabolite production, energy generation, and protein synthesis, crucial for tumor growth, while HPV-positive tumors focus on DNA repair and replication, potentially leading to genomic instability.…”
Section: Tumor Microenvironment (Tme) and Applied Immunotherapy In Hp...mentioning
confidence: 99%
“…HPV-negative tumors prioritize metabolite production, energy generation, and protein synthesis, crucial for tumor growth, while HPV-positive tumors focus on DNA repair and replication, potentially leading to genomic instability. 42 Recognizing these differences is vital for personalized treatment strategies in HNSCCs management.…”
Section: Tumor Microenvironment (Tme) and Applied Immunotherapy In Hp...mentioning
confidence: 99%